Correlation of upper incisor–manubriosternal joint length with upper incisor–carinal length to predict airway length in the pediatric population: An observational study - Thomas T Vellapally; Deepa Baskaran; Michelle Meril Reginald (Asian Journal of Medical Sciences, 2025)
Background: Short and variable length of the trachea precludes accurate placement of endotracheal tubes (ETTs) in the pediatric population. The incidence of malposition of the ETT in the pediatric population was reported to be 30–50% warranting repositioning. The manubriosternal joint (MSJ) and the carina lie in the same horizontal plane. This can be utilized as a guide during endotracheal intubation in children. Aims and Objectives: To evaluate the correlation between the incisor-MSJ (IMSL) length measured in extension and the incisor–carinal length (ICL) and to predict the airway length in the pediatric population. Materials and Methods: Fifty-seven children between the ages of 2 and 8 years were recruited for our study. The length of the IMSL was measured with a tape after inducing anesthesia with the neck fully extended. Following intubation with appropriately sized ETT, ICL was measured in neutral position as well as in flexion and extension using fiberscope and the corresponding measurements were taken. Results: There was a positive correlation between the two parameters. The mean ICL-N was 15.65±2.17 cm, and the mean IMSL distance in extension was 16.22±2.46 cm, which was found to be statistically significant with R2=0.799 (P<0.001). The airway length can be estimated by the formula: ICL (neutral)=2.828+0.790×IMSL (extension). Conclusion: The IMSL length can be used as a simple and accurate reference for predicting the airway length and the depth of insertion of ETTs in the pediatric population.